Stakeholder opinions of the student’s abilities during the research internship program - Romadhoni, Ita Fatkhur; Susila, I Wayan; Rijanto, Tri; Miranti, Mauren; Megasari, Dindy Sinta (Jurnal Pendidikan Teknologi Kejuruan, 2023)
Recently, there has been a gap between the skills needed by industry and learning materials in schools that still need to meet expectations. Research internship programs (RIP) viewing as a link that can eliminate these disparities. However, there is no conclusive proof of the learning results of the program. This study seeks to dig deeper into information based on a stakeholder's point of view on the quality of skills demonstrated by students in research internship programs. This research is qualitative. The case study method approach analyzes phenomena in the workplace according to assessment reporting in terms of stakeholder perceptions. Research informants consist of primary, supporting, and critical stakeholders. This paper uses triangulation techniques to reduce data, present data, and draw conclusions. The results of this study indicate that students' readiness and skills affect hard-skill performance but do not significantly affect the results of the research conducted. Stakeholder perception states that schools need more time to be ready to implement research internships based on Ministerial Decree Number 123/M/KPT/2019.